Self-Styling, Popular Culture, and the Construction of Global-Local Identity among Japanese Food Lovers in Purwokerto - Yusida Lusiana; P. M. Laksono; Tatang Hariri (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2020)
People are currently faced with the kaleidoscopic flux of dishes, that almost everyone encounters various foods from around the world, one of which is Japanese Food. The presence of Japanese food in Purwokerto City, Central Java is the consequence of the global power with its capability to produce thoughts and ideas, real or illusory, related to their products and all of which influence local values and cultures. This research studies the impacts of globalization as reflected in the formation of identity and lifestyle in connection with Japanese food consumption. The research’s objective is to study some powers the decision to consume Japanese food is based on from the perspective of popular culture’s influence. The research result shows that according to the participants, media and popular culture products contribute to the formation of layered identities. The globalization of Japanese food consumption culture does not produce cultural homogenization process, as one of many powers in the participants’ life, and media has encouraged heterogenization. Through the concept and practice of appropriation processes, Japanese food consumption has become part to communicate their cultural identity. The presence of Japanese food is one factor of the emergence of a new lifestyle, namely “Japanese lifestyling”, which is one lifestyle practiced by some people of Purwokerto which serves to enrich its consumers’ identity to be individuals who attempt to embrace the world through eating experience.